On the Political Economy of Environmental Policy - Gebhard Kirchgässner; Friedrich Schneider (Center for Economic Studies and ifo Institute (CESifo), 2002)
In the past there was hardly any use of economic instruments in environmental policy, mainly command and control measures were used. More recently, ecological taxes as well as tradable permits became more popular and voluntary agreements have been implemented. Using the Public Choice approach we ask for the reasons of this wider acceptance of economic instruments. We conclude that the use of market based instruments in environmental policy has not increased very much and their impact on the actual situation is still rather low, but there is hope of at least some increase in the future.
Keywords: Q00; 330; environmental policy; ecological taxes; tradable permits; voluntary agreements; voting behaviour; public bureaucracy; interest groups; Umweltpolitik; Public Choice; Theorie